2016
DOI: 10.1370/afm.1953
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Ankle Swelling: Population Symptom Reporting Using Google Trends

Abstract: In our experience, complaints of ankle swelling are more common in summer, typically from patients with no obvious cardiovascular disease. Surprisingly, this observation has never been reported. To objectively establish this phenomenon, we sought evidence of seasonality in the public's Internet searches for ankle swelling. Our data, obtained from Google Trends, consisted of all related Google searches in the United States from January 4, 2004, to January 26, 2016. Consistent with our expectations and confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“… 15 , 16 And, a recent analysis found that public interest in ankle swelling, as measured as Google search volume, is highly seasonal, with peaks in summer in the USA and Australia. 5 Altogether, these trends may help us to understand why cellulitis is more common in summer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 , 16 And, a recent analysis found that public interest in ankle swelling, as measured as Google search volume, is highly seasonal, with peaks in summer in the USA and Australia. 5 Altogether, these trends may help us to understand why cellulitis is more common in summer.…”
Section: Discussionmentioning
confidence: 99%
“…The monthly data were plotted according to time for each of the 31 countries and regression analysis was performed using GraphPad Prism 7 (GraphPad Software Inc., La Jolla, CA, USA). The regression analysis was carried out with a seasonal model, as described previously, 5 , 8 consisting of a straight line function and a sinusoid function as follows: …”
Section: Methodsmentioning
confidence: 99%
“…In our study, the effect of weather on DAS in the summer can be explained by the relevant observed effect of meteorological parameters on subjective DAS components (TJC and VAS). In addition, the frequent tissue inflation observed in the summer [ 20 ] may potentially increase SJC and explain the observed DAS effect.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the United Kingdom and Australia, the volume of searches related to leg cramps increased in summer [ 25 ]. Another study found that searches related to ankle swelling also increased in midsummer [ 26 ]. Heartburn-related searches increased during winter, as did heart failure hospitalizations [ 10 , 27 ].…”
Section: Discussionmentioning
confidence: 99%